Advances in Molecular Techniques - Sengar, Rakesh S.
"Molecular genetics aims to comprehend biological activity at the gene sub-level. Scientists from different areas of research and applied science can use the standard techniques optimized by molecular biologists. This book serves as a guide that introduces classic molecular biology techniques and advances in molecular and genetic engineering."--Provided by publisher.